Actants In James Dashner's The Maze Runner: An A. J. Greimas Naratological Study - Bayu Enggar Sasono; Agung Suhadi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to describe the actant in The Maze Runner novel based on the scheme of the actant, and the structure of the story. Methods of data collection is done by reading notes technique. This study uses content analysis because it prioritizes the depth of appreciation of the interactions between concepts that are being studied empirically. The results of the research show that there are three acts which are divided into three chapters in this novel. The actant and functional structures in The Maze Runner novel are complex and have fulfilled all stages. This novel can be used as literature learning material, especially novels.